Literatur Falsafah Islam di Indonesia Buah Karya para Penulis Indonesia - Nanang Tahqiq (Jurnal Lektur Keagamaan, 2015)
Artikel ini melukiskan sekaligus memetakan susunan dan gambaran buku-buku falsafah Islam di Indonesia sejak awal kemunculan. Kajian ini menelaah secara sequence analysis, yakni menyajikan pustaka-pustaka falsafah Islam di Indonesia secara berurut menurut tahun pertama kali terbit. Guna membagi penjelasan distinktif mengenai falsafah Islam, maka tulisan ini membedakan tiga istilah: 1) falsafah Islam, 2) falsafah Islam di Indonesia, dan 3) falsafah Islam Indonesia. Penelitian ini mendeduksikan bahwa buku-buku falsafah Islam di Indonesia belum menguak materi dasar falsafah Islam itu sendiri.Kata Kunci: asas-asas falsafah Islam, pustaka falsafah Islam, falsafah Islam di IndonesiaThis article portrays, and all together, provides a map and illustration of literatures of Islamic philosophy in Indonesia, from the earlier moment when they appeared. This enquiry scrutinizes the subject by using analytical sequence, i.e. to present the books of Islamic Philosophy in Indonesia sequentially based on their first publication. In order to elucidate distinctively about Islamic philosophy, this study differentiates three terms: 1) Islamic philosophy, 2) Islamic philosophy in Indonesia, and 3) Indonesian Islamic philosophy. This study deduces that Islamic philosophical literatures have not revealed the basic matters of Islamic philosophy.Keywords : principles of Islamic philosophy, literature of Islamic philosophy, Islamic philosophy in Indonesia